Mona mousa code - Stilton, Geronimo (New Delhi Scholastic, 2024)
Do you like solving mysteries? I do! So when my sister-Thea-heard that there was a secret hidden in Mouse Island's most famous painting the Mona Mousa. I knew we had to crack the code! We began to Investigate and soon as we were following a trail of clues that led us below the streets of the New Mouse City. There we made the most fabulous discovery.
Keywords: Children Fiction